Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di Desa Tanjung dalam Wilayah Kerja Puskesmas Lubuk Batang OKI Tahun 2021 - Muntiara Muntiara; Rizki Amalia; Syarifah Ismed (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Exclusive breastfeeding is breast milk that is given to babies from birth for six months, without adding and replacing it with other foods or drinks (except drugs, vitamins, and minerals). This study aims to determine the relationship between knowledge, work and family support with exclusive breastfeeding in Tanjung Dalam Village, Lubuk Batang Health Center Work Area, Lubuk Batang District, Ogan Komering Ulu Regency in 2021. The design of this study is an analytical survey using a cross sectional research design. The population in this study were all mothers who had babies aged 7-12 months as many as 38 respondents and the number of samples as many as 38 respondents. The sampling technique used is Accidental Sampling. Data analysis used chi square statistical test with p value value (0.05). The results of this study from 35 respondents, it was found that there was a relationship between knowledge (p value = 0.005), occupation (p-value = 0.01) and family support (p-value = 0.02) with exclusive breastfeeding. Midwives are expected to increase counseling and socialize the exclusive breastfeeding program to the community.